THEY ARE IN THE QURAN - Poppy Hippy; Mardan; Muhammad Yusuf (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Human rights are rights that are owned by all people according to humane conditions. These human rights are always seen as something basic, fundamental and important. Therefore, the opinion that says that human rights are "power and security" owned by every individual. The idea of ​​human rights arose in the 17th and 18th centuries, as a reaction to the absolutism of kings and feudal lords at that time towards the people they ruled or the people they employed, namely the lower class society, this lower class society did not have rights, they were treated arbitrarily as slaves owned. As a reaction to this situation, the idea arose so that the lower class society would be elevated from its position as slaves